2018
DOI: 10.1111/jdi.12961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral magnesium sulfate administration on lectin‐like oxidized low‐density lipoprotein receptor‐1 gene expression to prevent atherosclerosis in diabetic rat vessels

Abstract: Aims/Introduction The purpose of the present study was to investigate the possible effect of oral magnesium sulfate (Mg SO 4 ) in the reduction of atherosclerosis plaques through inhibition of lectin‐like low‐density lipoprotein receptor‐1 ( LOX‐1 ) gene expression in diabetic vessels. Materials and methods A total of 50 rats were divided into five groups, including non‐diabetic control, Mg‐treated non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Based on our previous studies 19,20 in chronic diabetic animal models, it was shown that oral administration of MgSO 4 could dilate the vessels and improve atherosclerosis. It is not clear how Mg reduces atherosclerosis, but according to our previous findings, Mg is likely to improve atherosclerosis by reducing plasma oxLDL level and its receptor in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our previous studies 19,20 in chronic diabetic animal models, it was shown that oral administration of MgSO 4 could dilate the vessels and improve atherosclerosis. It is not clear how Mg reduces atherosclerosis, but according to our previous findings, Mg is likely to improve atherosclerosis by reducing plasma oxLDL level and its receptor in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear how Mg reduces atherosclerosis, but according to our previous findings, Mg is likely to improve atherosclerosis by reducing plasma oxLDL level and its receptor in endothelial cells. 19 Moreover, hypomagnesemia increases the intracellular calcium level. Ca plays an important role in signaling pathways such as activation of NMDA receptor, which, in turn, causes the release vasoconstrictor agents, increase lipid peroxidation and NF-κB activation in smooth arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation